THE CONCEPT OF SUSTAINABLE DEVELOPMENT OF THE REGIONS - Akbar Safarov (American Journals Publishing, 2022)
The article substantiates the theoretical foundations for applying the concept of sustainable development in the region. The object of sustainable development is formulated, the criteria for assessing sustainable development are determined.
Keywords: development, education, society, globalization, state, economy.